Cooperation in WTO's Tariff Waters? - Marcelo Olarreaga; Alessandro Nicita; Peri Silva (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
This paper examines the extent to which tariff cooperation is observed among World Trade Organization (WTO) members. With the help of a simple political economy model, we show that tariffs are positively correlated with the importer's market power when they are set non-cooperatively, but negatively correlated when set cooperatively. We use this prediction to empirically identify the extent of cooperation in the WTO, and find that more than three quarters of WTO members' tariffs are set non-cooperatively. Keywords: Export supply elasticities, WTO cooperation, tariff water
Keywords: F13; 330